Perancangan Dashboard untuk Alat Bantu Monitoring Kualitas dan Pemenuhan Regulasi Keamanan Pangan di PT SMART Tbk - Hendry Adrianus (Jurnal Titra, 2020)
PT SMART Tbk is a company engaged in the palm oil processing industry. Products produced by PT SMART Tbk includes cooking oil, margarine, shortening and specialty fats. PT SMART Tbk has been distributing their products to the international level, so raw materials, food additives, processing aids, packaging materials and products produced must be able to meet all applicable food safety regulations both in Indonesia and internationally. The numbers of food safety regulations that applys in both countries make the companies to require tools which can help in monitoring the quality and compliance of food safety regulations. The purpose of this study is to design a dashboard that can be used to monitor the quality and compliance of food safety regulations for each raw material, food additives, processing aids, packaging materials and products. The dashboard design is made using Microsoft excel and VBA. The results of this study is a dashboard that can show ingredients or products that don’t meet food safety regulations, also it conduce a list of regulations that can help companies to know maximum limit use of raw materials, food additives, processing aids, packaging materials for products as well as product specifications that may be distributed to consumers.